Cancer risk from medical radiation / Nurul Annisa Ramli ... [et al.] - Ramli, Nurul Annisa; Fadzil, Nur Farhan Natasha; Muhamad Fauzi, Nursuhaila; Mohd Nasir, Nur Azlin Atikah; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan; Mat Nazir, Eliy Nazira; Azizan, Muhammad Nashiruddin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Every day people come into contact with radiation sources whether they are man-made or natural. Natural materials from within the earth and cosmic rays from space are sources of radiation. In contrast, manmade sources of radiation such as X-rays are often used for airport security scanners, medical imaging, cancertreatment and food irradiation. In the field of medicine, medical radiation is a type of radiation used to treat diseases or perform various diagnostic operations. X-rays and gamma rays are electromagnetic radiation that have a high frequency and energy. In terms of physics, these two types of radiation have similarities such as being uncharged, having no mass and causing the same biological effects on the human body.